The development and applications of a child-centred Well-Being Index : findings from a longitudinal project using data from the Growing Up in Ireland study - Taut, Cristina (Trinity College (Dublin, Ireland). Department of Public Health and Primary Care, 2017)
The children of today are the adults of tomorrow. Therefore, children's well-being is relevant for the current and future society. In this context, the study of well-being of children and young people has received great national and international interest over the last decade and several studies aiming to develop a measure, or index, of child well-being at an individual or population level have emerged. Such well-being indices may be used by child advocacy groups, policy makers, researchers, the media, and service providers to describe the condition of children, to monitor or track child outcomes and to set goals for the future. In line with the national and international trends the overarching aim of this project was to construct a child-centred Well-Being Index for Irish children. A "whole child" perspective was adopted and well-being was viewed as an expression of a child's physical, social, emotional and intellectual functioning, and was investigated in relation to developmental determinants reflecting aspects from a child's life known to influence early development.
Keywords: Public Health & Primary Care Ph.D.; PhD Trinity College Dublin, 2017